Activated Platelets Convert CD14+CD16- Into CD14+CD16+ Monocytes With Enhanced FcγR-Mediated Phagocytosis and Skewed M2 Polarization - Lee, Su Jeong; Yoon, Bo Ruem; Kim, Hee Young; Yoo, Su-Jin; Kang, Seong Wook; Lee, Won-Woo (Frontiers in Immunology, 2021)
Monocytes are important cellular effectors of innate immune defense. Human monocytes are heterogeneous and can be classified into three distinct subsets based on CD14 and CD16 expression. The expansion of intermediate CD14+CD16+ monocytes has been reported in chronic inflammatory diseases including rheumatoid arthritis (RA). However, the mechanism underlying induction of CD16 and its role in monocytes remains poorly understood. Here, we demonstrate that activated platelets are important for induction of CD16 on classical CD14+CD16- monocytes by soluble factors such as cytokines. Cytokine neutralization and signaling inhibition assays reveal that sequential involvement of platelet-derived TGF-β and monocyte-derived IL-6 contribute to CD16 induction on CD14+CD16- monocytes. Activated platelet-induced CD16 on monocytes participates in antibody-dependent cellular phagocytosis (ADCP) and its level is positively correlated with phagocytic activity. CD14+CD16- monocytes treated with activated platelets preferentially differentiate into M2 macrophages, likely the M2c subset expressing CD163 and MerTK. Lastly, the amount of sCD62P, a marker of activated platelets, is significantly elevated in plasma of RA patients and positively correlates with clinical parameters of RA. Our findings suggest an important role of activated platelets in modulating phenotypical and functional features of human monocytes. This knowledge increases understanding of the immunological role of CD14+CD16+ cells in chronic inflammatory diseases.